H‐bond and electric field correlations for water in highly hydrated crystals. Issue 2 (15th January 2016) - Sen, Anik; Mitev, Pavlin D.; Eriksson, Anders; Hermansson, Kersti
Abstract : We present periodic plane‐wave density functional theory (DFT) Perdew–Burke–Ernzerhof (PBE‐D2) calculations for four highly hydrated crystals, Na2 CO3 ·10H2 O, MgSO4 ·7H2 O, MgSO4 ·11H2 O, and Al(NO3 )3 ·9H2 O, containing 37 structurally unique water molecules and 74 unique hydrogen bonds. The calculated R (H···O) distances lie in the range 1.60–2.05 Å, the anharmonic OH frequencies in the range 2570–3425 cm −1, and the water dipole moments lie in the range 2.9–4.3 Debye, as calculated from the Wannier function centers and the nuclei. We present the following findings. (i) Our optimized intramolecular r (OH) distances are always larger than the gas‐phase value and thus more accurate than those derived from neutron diffraction experiments; (ii) The local in situ electric field over the molecule, calculated from the positions of the nuclei and the Wannier centers in the surrounding crystal, appears to be a good descriptor of the pertturbation from the water molecule's surroundings as the internal molecular properties ( r e, ν, μ ) are found to correlate well with the crystal‐generated electric field; (iii) We have added DFT‐calculated data points to the well‐known experimental 'OH frequency versus R (H···O)' correlation curve in a region where the experimental data points are scarce; (iv) For all 37 water molecules, the Wannier centers located in the lone‐pair region, and those located in the OH bonds, displace about equally much due to the polarizing environment. Finally, we propose that our resulting 'OH frequency versus Wannier‐type electric field' correlation curve may constitute a useful tool for predicting OH vibrational frequencies from snapshots from PBE‐D2‐based ab initio molecular dynamics simulations of water‐containing systems. © 2015 Wiley Periodicals, Inc. Abstract : Periodic plane‐wave density functional calculations are applied to the study of highly hydrated crystals, containing 37 unique water molecules with 74 unique H‐bonds. A number of H‐bond correlations are derived, among them an 'OH frequency versus Wannier‐type electric field' correlation curve that is proposed to be used for predicting OH vibrational frequencies from snapshots from PBE‐D2‐based AIMD simulations of water‐containing systems.